Breast cancer genetic susceptibility: With focus in Saudi Arabia - Fawaz D. Alshammari (Journal of Oncological Sciences)
In recent years there have been important advances in molecular genetics and linkage analysis of the breast cancer. Beside germline BRCA1 or BRAC2 mutations, and somatic genetic alterations, epigenetic alterations in numerous genes play an essential role in the tumorigenesis of breast cancer. TP53, STK11, PTEN, CDH1, NF1 or NBN mutations are associated with high breast cancer associated syndromes. Mutations in DNA repair associated genes (ATM, CHEK2, BRIP1, PALB2 and RAD50) are associated with increased breast cancer risk. Moreover, several single nucleotide polymorphisms (SNPs) were considered as breast cancer susceptibility polymorphisms within genes (FGFR2, TOX3, LSP1, MAP3K1, and TGFB1). This review discusses breast cancer genetic susceptibility, highlights recent advances in breast cancer genetics, with a particular focus in Saudi women. Keywords: Breast cancer susceptibility, Single nucleotide polymorphisms (SNPs), Breast cancer genetics, Hereditary breast cancer